Kontribusi Ekonomi Hijau terhadap Keberlanjutan Pengelolaan Sumber Daya Alam di Indonesia: Penelitian - Bonaraja Purba; Pany Iglesia M Simamora; Yesi Veronika Simarmata; Feny Amelia Sinaga; Diana Winata Lumban Gaol (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study discusses the contribution of the green economy to the sustainability of natural resource management in Indonesia through qualitative approach based on literature studies. The green economy is seen as a development strategy that integrates economic growth, environmental protection, and social justice.The implemantation of these policies contributes to reducing greenhouse gas emissions by up 29% according to the 2030 Nationally Determined Contribution (NDC) target, increasing energy and water efficiency, and creating up to 10 million green jobs as projected by the ILO. However, the main challenges include regulatory inconsistencies between the central and regional goverments, limited green funding, and the law realizaation of renewable energy in the national energy mix. This study recommends harmonization of cross-sectoral policies, strengthening green financing schemes, and increasing public awareness of the green transition. The results of this study confirm that the green economy is a strategic invesment in realizing the vision of a golden Indonesia 2045 that is competitive, resilient, and ecologically sustainable.